Aplikasi Teknologi Penetasan Dalam Rangka Peningkatan Populasi Ternak Itik di Kecamatan Simbang Kabupaten Maros Provinsi Sulawesi Selatan - Daryatmo Daryatmo; M. Rachman Hakim; Wempie Pakiding (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2020)
The purpose of this community partnership program were to provided the knowledge and skills of duck breeder communities in Maros Regency, especially in the hatchery aspect. Community service activities begin with a socialization stage to identify problems under supervision, observe training and mentoring, and post achievement activities. Through the stages of training activities, the service provider together with the breeders implements good hatching egg selection, applies the hatching of eggs using a hatching machine and is followed by handling post-hatch ducks. The level of participation in activities is quite high, with the participation of all breeders during service activities. It is hoped that this activity will increase the livestock population so that the income of breeders can be improved and improve the welfare of the community. In addition, community service activities that have been carried out support local government programs in developing duck livestock populations in the Simbang District, Maros Regency.